GABA Release and Uptake Regulate Neuronal Precursor Migration in the Postnatal Subventricular Zone - Bolteus, Anna J. (J Neurosci, 2004)
In the postnatal subventricular zone (SVZ), astrocyte-like cells tightly encapsulate chains of migrating neuronal precursors, although an influence of the astrocyte-like cells on precursor migration has not yet been demonstrated. Cell migration was studied in acute sagittal brain slices to determine whether GABA signaling between astrocyte-like cells and neuronal precursors controls the speed of neuronal precursor migration in the anterior SVZ and rostral migratory stream of juvenile and adult mice. Application of GABA at 10 μm, a nondesensitizing concentration for GABA(A) receptors (GABA(A)Rs), reduced the rate (mean of ∼50 μm/hr) of cell migration by 21% via GABA(A)R activation. Application of the GABA(A)R antagonist bicuculline enhanced the migration rate by 30%, suggesting that endogenous GABA tonically reduces the speed of cell migration via GABA(A)R activation. Using immunohistochemistry, we found that astrocyte-like cells express the high-affinity GABA transporter subtype GAT4 on processes ensheathing neuronal precursors that contain GABA. Inhibition of GABA uptake into astrocyte-like cells or enhancement of GABA release from neuronal precursors during high K(+) application further reduced the migration rate by increasing ambient GABA levels. GABA altered the migration speed by interfering with intracellular Ca(2+) signaling independently of cell depolarization, because high K(+) application did not alter the speed of cell migration in the presence of bicuculline. These data indicate that astrocyte-like cells create a microenvironment in which their uniquely positioned GABA transporters control the degree of GABA(A)R activation and the migration of neuronal precursors.